Jardín infantil (2017)
The architectural project of the kindergarten is part of the proposed urban renewal proposed for the San Felipe neighborhood in northeastern Bogota, which seeks to reactivate the area and enhance the importance of the place as a result of the implementation of the metro system on the avenue La Caracas, being the 72nd street the auction station of the first stage. Taking into account the residential character of the neighborhood, it is proposed that the project cover the demand for early childhood education that the sector needs, supported by other uses that respond to the flows generated by the high meter. As a project intention is planned that the kindergarten is a magical world within a real world where the limits of the property are adopted as a barrier or door of the real world to the imaginary inner world, where there are no limits in the spaces thus generating in children The opportunity to experience and learn in an unconventional creative environment.--Tomado del Formato de Documento de Grado.